2018
DOI: 10.1029/2018jb015998
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Thermal Structure of Oceanic Lithosphere With Revised Global Inventories of Basement Depths and Heat Flow Measurements

Abstract: Half‐space cooling and plate models of varying complexity have been proposed to account for changes in basement depth and heat flow as a function of lithospheric age in the oceanic realm. Here, we revisit this well‐known problem by exploiting a revised and augmented database of 2,028 measurements of depth to oceanic basement, corrected for sedimentary loading and variable crustal thickness, and 3,597 corrected heat flow measurements. Joint inverse modeling of both databases shows that the half‐space cooling mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(179 citation statements)
references
References 111 publications
(267 reference statements)
7
172
0
Order By: Relevance
“…The resulting seafloor subsidence is significantly different from that predicted by GDH1 for age >65 Ma but in good agreement with Sclater () Model (PS; Figure ) or the more recent analysis of Richards et al (), which selected 2,028 reliable sites where sediment thickness and crustal thickness are well known. In order to check if these differences were related to methodological problems, the same analysis was performed using just the global topography (GTOPO30).…”
Section: Oceanic Heat Flowsupporting
confidence: 79%
“…The resulting seafloor subsidence is significantly different from that predicted by GDH1 for age >65 Ma but in good agreement with Sclater () Model (PS; Figure ) or the more recent analysis of Richards et al (), which selected 2,028 reliable sites where sediment thickness and crustal thickness are well known. In order to check if these differences were related to methodological problems, the same analysis was performed using just the global topography (GTOPO30).…”
Section: Oceanic Heat Flowsupporting
confidence: 79%
“…Mapping the lithosphere-asthenosphere boundary (LAB). A recent study on the thermal structure of oceanic lithosphere found that the 1175 ± 50 • C isotherm provides a good match to seismological observations of the lithosphere-asthenosphere boundary (Richards et al, 2018). In this study, we therefore adopt this isotherm as a proxy for lithospheric thickness beneath the continents.…”
Section: Mineral System Implicationsmentioning
confidence: 86%
“…For each rift scenario, we select an initial lithospheric template. For regular continental lithosphere, the crustal thickness is set to 30 km and the total lithospheric thickness to 140 km, which matches results from plate cooling models of oceanic lithosphere (Richards et al, 2018) and places the 1175 • C isotherm at ∼ 120 km. Radiogenic heat production in the mantle is set to zero, whilst the crustal value is tuned to 1.0 µW m −3 such that the steady state geotherm yields a surface heat flow of ∼63 mW m −2 , which is the average for Phanerozoic continental lithosphere (Lucazeau, 2019) For cratonic lithosphere, we assume an initial crustal thickness of 50 km, lithospheric thickness of 280 km (1175 • C isotherm at ∼ 240 km), and crustal radiogenic heat production of 0.57 µW m −3 , which yields an initial surface heat flux consistent with the average of ∼48 mW m −2 for Archean and cratonic areas (Lucazeau, 2019) Based on the typically low paleowater depth of sediments found in proximal portions of these basins and the high supply of clastic material from adjacent cratons, we assume the basin is constantly filled by sediments.…”
Section: Mineral System Implicationsmentioning
confidence: 99%
See 2 more Smart Citations